VITAMIN D–VITAMIN D RECEPTOR AXIS IN BREAST CANCER: MECHANISMS, EVIDENCE, AND CLINICAL IMPLICATIONS - VEMURI HELENA; ARUMUGAM SURESH; KUPPUSAMY BASKARAN; NATRAJAN MUNINATHAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
The Vitamin D-Vitamin D receptor (VDR) axis is biologically important in breast cancer because breast tissue can locally activate and break down Vitamin D, allowing direct control of cell growth, death, DNA repair, and the tumor microenvironment. In many breast cancers, this system is disturbed, with reduced effective VDR signaling and altered Vitamin D-metabolizing enzymes, changes that tend to appear in more aggressive disease. Experimental studies show that activating VDR can slow proliferation, limit stem-like behavior, reduce invasion and metastasis, and help maintain genomic stability and balanced immune responses. Human data generally link low blood Vitamin D levels and a disrupted VDR pathway with higher breast cancer risk and poorer outcomes, especially in hormone receptor-positive and some triple-negative or BRCA1-related tumors, although these patterns are weakened by lifestyle confounding and mostly neutral prevention trials. At present, the most realistic clinical use is routine testing and correction of Vitamin D deficiency, mainly for bone and general health, with any anticancer benefit framed as possible but unproven. Future work should focus on biomarker-guided, subtype-specific trials that combine Vitamin D-based approaches with endocrine, cytotoxic, or other targeted therapies, positioning the Vitamin D-VDR axis as a precision co-modulator rather than a stand-alone treatment.